Targeting inflammation in diabetic nephropathy: a tale of hope. (2nd November 2018) - Moreno, Juan Antonio; Gomez-Guerrero, Carmen; Mas, Sebastian; Sanz, Ana Belen; Lorenzo, Oscar; Ruiz-Ortega, Marta; Opazo, Lucas; Mezzano, Sergio; Egido, Jesus
ABSTRACT: Introduction : Diabetic nephropathy (DN) is the leading cause of chronic kidney disease (CKD) and end-stage renal disease (ESRD). Beyond the new anti-diabetic drugs that possess markedly cardiovascular and renal protective effects, no novel direct therapies for DN have become available on the market in the last twenty years. Recently well-designed clinical trials for the treatment of DN, with attractive pathogenetic rationale, e.g. bardoxolone and atrasentan, were canceled or stopped because of safety concerns or lack of reaching the end points, respectively. Areas covered : In this review, we focus on the involvement of inflammation in the pathogenesis of DN. We update information from recent experimental and clinical studies that reported beneficial effects of several agents targeting chemokines, cytokines, transcription factors and kinases as well as several compounds with anti-inflammatory properties on DN. Expert opinion : Inflammation plays a key role in the DN progression. Preclinical studies have identified several anti-inflammatory molecules that effective decrease albuminuria and/or proteinuria. However, limited clinical trials in humans have been performed to confirm these results. Inhibitors of CCL2/CCR2, IL-1β and JAK/STAT pathways, and Nrf2 inducers are promising therapeutic options to improve the renal outcome of patients with DN, but appropriate clinical trials are necessary.